Mapping Groundwater Vulnerability in Arid Regions: A Comparative Risk Assessment Using Modified DRASTIC Models, Land Use, and Climate Change Factors - Simone A. Williams; Sharon B. Megdal; Adriana A. Zuniga-Teran; David M. Quanrud; Gary Christopherson (Land)
Groundwater vulnerability in arid regions is increasingly influenced by land use changes and climate variability. This study evaluates groundwater vulnerability and contamination risk in the arid/semi-arid Verde River Basin and Prescott Active Management Area using four models: DRASTIC, DRASTIC-LUCC, DRASTIC-LUCC-AHP2, and DRASTIC-LUCC-AHP4. Modifications to the traditional DRASTIC model, including the integration of land use and climate factors and the application of AHP (Analytic Hierarchy Process) to refine variable weighting, significantly enhanced predictive accuracy. Results demonstrate that models incorporating land use and climate data outperform the traditional approach. The DRASTIC-LUCC model identified elevated nitrate concentrations in high-vulnerability areas, while DRASTIC-LUCC-AHP2 exhibited the greatest sensitivity in classifying vulnerability. Karst aquifers were particularly susceptible due to their high permeability and rapid contaminant transport. Recommendations include routinely integrating land use and climate data into vulnerability assessments, enforcing land use controls in high-risk zones, promoting adaptive management practices, and raising public awareness to mitigate contamination risks. This framework offers actionable strategies for improving groundwater protection and sustainable management in arid and semi-arid regions facing water security challenges.